(untitled) (Journal of actual problems of jurisprudence, 2018)
The article briefly describes the problem of gaps environmental legislation, in light of the Message of the President of the Republic of Kazakhstan Nursultan Nazarbaev «Kazakhstan’s way -2050 «, its priorities and some possible legal development of the country in the coming period. The author believes that the new Message will be better integrated into a single system of jurisprudence and practice, legal education and legal education in the field of environmental law, will create additional opportunities for constructive interaction between the state and civil society. Key words: law violations, responsibility, the «green» economy, ecology.